2021
DOI: 10.26832/24566632.2021.0603017
|View full text |Cite
|
Sign up to set email alerts
|

Status of forest soil and necessity of sustainable soil conservation practices of Nepal

Abstract: Forests are the fundamental natural resource regarded as the crucial aspect to uplift rural livelihood in Nepal. Forest, not only acquaints us with ecosystem services but also deals with carbon sequestration and nutrient cycling in forest soil, serving the most crucial part of human welfare. However, several human forces such as construction of roads, deforestation, shifting cultivation, overgrazing, and forest fires have decreased the organic matter content and contributed to landslides, erosion and sedimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…These factors can also influence dependence on forest resources. Based on these findings, forestry programs could benefit from incorporating support mechanisms for older adults who rely on forest resources [ 39 ]. This could help ensure their well-being and promote sustainable forest management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors can also influence dependence on forest resources. Based on these findings, forestry programs could benefit from incorporating support mechanisms for older adults who rely on forest resources [ 39 ]. This could help ensure their well-being and promote sustainable forest management.…”
Section: Resultsmentioning
confidence: 99%
“…This aligns with the findings of Acharya et al [ 40 ], who reported a positive association between education and willingness to pay for forest benefits. This could be due to limited alternative income opportunities in the study area, emphasizing the importance of considering local context when interpreting the impact of educational attainment on forest dependence [ 39 ].…”
Section: Resultsmentioning
confidence: 99%